2009
DOI: 10.1111/j.1365-2648.2008.04891.x
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian nurses’ knowledge and practice of breast self‐examination

Abstract: More health education about monthly breast self-examination and prevention strategies is needed for nurses and their women patients, especially for Arabic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 5 publications
5
28
0
Order By: Relevance
“…The findings were similar to studies conducted among Norwegian female physicians and Jordanian nurses in Egypt who stated similar reason for not performing BSE (Alkhasawneh et al, 2009).…”
Section: Discussionsupporting
confidence: 79%
“…The findings were similar to studies conducted among Norwegian female physicians and Jordanian nurses in Egypt who stated similar reason for not performing BSE (Alkhasawneh et al, 2009).…”
Section: Discussionsupporting
confidence: 79%
“…While many studies found those who had relatives with BC had better knowledge (Madanat and Merrill 2002;Sreedharan et al, 2010). Insufficient knowledge on some risk factors among PHCC nurses may indicate that some nurses were not updating their information or were not directly involved in patient education as indicated in Alkhasawneh's (2009) study. The findings of this study showed the importance of continue education (CE) for the PHCC nurses to promote early detection and prevention of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that doctors often do not offer BCS services to women. Other health care providers (HCP) might not have adequate knowledge of BCS and risk factors related to breast cancer in the Middle East, thus limiting their ability to encourage patients to engage in BCS activities (Bener et al, 2001;Haji-Mahmoodi, 2002;Madanat and Merrill, 2002;Dow Meneses and Yarbro, 2007;Alkhasawneh et al, 2009;Jaradeen, 2010;El Hajj and Hamid, 2011). Previous studies in the region indicate low participation rates in breast cancer screening activities among women (Bener et al, 2001;Bener et al, 2002;Azaiza and Cohen, 2008;Bener et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and varied sources of information about breast health and BCS from health care providers (especially physicians), mass media, and social networks can positively influence women's knowledge and practice of BCS (Al-Qattan, et al, 2007;Dandash and Al-Mohaimeed, 2007;Montazeri, et al, 2008;Hoffman et al, 2010). Facilitators of BCS behavior include having support from male relatives, receiving information about breast cancer or BCS from health care professionals (HCP) other than doctors, and having a doctor's recommendation (Haji-Mahmoodi, 2002;Madanat and Merrill, 2002;Cohen and Azaiza, 2005;Azaiza and Cohen, 2006;Shirazi et al, 2006;Dandash and Al-Mohaimeed, 2007;Dow Meneses and Yarbro, 2007;El Saghir et al, 2007;Alkhasawneh et al, 2009;Gürsoy et al, 2009;Jaradeen, 2010;El Hajj and Hamid, 2011).…”
Section: Introductionmentioning
confidence: 99%